The Influence of Green Marketing, Consumer Knowledge and Purchasing Power on Environmental Attitudes - Maulana, Ahmad; Indrajaya, Nehemia; Novalia, Nurkardina (Integrated Journal of Business and Economics (IJBE), 2025)
Global changes in the modern industrial era encourage the importance of environmental sustainability, triggering the popularity of green marketing as a key strategy for companies to advertise sustainable goods. In this dynamic, the level of consumer knowledge and purchasing power also are essential in influencing consumer preferences and choices regarding sustainable products. This study aims to understand the influence of green marketing, consumer knowledge, and purchasing power on environmental attitude in Indonesia, particularly in the Southern Sumatra region. The gathered data of 118 participants were examined through the partial least squares structural equation modeling (PLS-SEM) method to evaluate the proposed hypotheses. The findings revealed that green marketing and purchasing power exert a direct and significant impact on environmental attitude, suggesting that marketing efforts and financial capability play a key role in shaping consumer perceptions of sustainability. In contrast, consumer knowledge does not have a significant direct effect on environmental attitude, indicating that awareness alone may not be sufficient to drive environmentally responsible behavior. These findings contribute to the understanding of factors influencing consumers' environmental attitudes, provide strategic direction for companies aiming to enhance green product adoption, and stimulate further discussion on sustainability practices in Southern Sumatra.